A Bibliometric Analysis the Scope of Local, Global, And Glocal Studies - Ismail, Ahmad; Munsi, Hardiyanti; Yusuf, Andi Muhammad (Faculty of social and Political sciences, Hasanuddin University, 2024)
This article seeks to employ bibliometric analysis to offer a thorough picture of the research environment concerning local, global, and glocal contexts. Amidst the increasing globalization, it is imperative to deeply understand the interplay between local and global contexts and the